Magnetic Susceptibility Signature Technique: A Viable Clay Typing Tool for Sustainable Road Constructions in Some Parts of Niger Delta - Asime, Orudukobipi; Lawson, Chioma Don (New Innovations in Chemistry and Biochemistry Vol. 7, 2022)
The essentials of science and technology as tools for proffering solutions for problems affecting man and societal development cannot be overlooked. The dilapidated states of roads in the Niger Delta region are major concerns on Nigeria Governments that desire the best for her citizens. Several strategies and techniques have been employed by successive Governments in the region in proffering solutions to avert such poor road conditions but none was sustainable in test of time. This work aimed at presenting magnetic susceptibility signature technique as a viable clay typing tool for sustainable road construction in some parts of Rivers State in the Niger Delta region, Nigeria. Samples were taken at random points in two sources A and B, as well as on two roads that were proposed to be built as sites X and Y. The samples were subjected to Volume Magnetic Susceptibility (VMS) measurements (S.I unit) using an MS2E Bartington instrument with built–in Bartsoft software, and their corresponding Magnetically Derived Illite (MDI) contents (percent) were calculated using Potter's Two Mineral Mixture Model. The MDI contents (percent) of the sources and sites were plotted against depth (m), and their spectra were compared for compatibility and sustainability. The Volume Magnetic Susceptibility (VMS) ranges from (0.8-118.0) x 10-5 for Source A and (45-300) x 10-5 for Site X,(7.6-227.0)x10-5 for Source B and (56.5-183.8)x 10-5 for Site Y. The MDI ranges from 3.8%-300.0% for Site X and 14.1%-290.5% for Site X. The findings showed that clays from source A and Site X, as well as those from Source B and Site Y, are compatible and cost-effective, however clays from Source A on Site Y and Source B on Site X are incompatible and uneconomical. The findings of this study can be applied by construction companies in the Niger Delta and elsewhere.